Poetics and Politics: The Use of Poetry as War Propaganda during the World Wars - Fioravanti, Vitória Ávila (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2022)
This paper aims to critically analyse and discuss the use of poetry as war propaganda during World War I and World War II considering the distinct cases of Rupert Brooke’s “The Soldier”, Thomas Hardy’s “Men who March Away”, and Ezra Pound’s “Canto 46”, which was read by the author himself during one of his Radio Rome broadcasts in 1942. While Brooke, similarly to other young soldiers who saw in the war a chance of fulfilling their patriotic duty and achieving glory, wrote verses clearly marked by his personal idealism, Thomas Hardy had many of his war poems commissioned by the British government in the context of a national propaganda effort in which he might have agreed to participate moved by his initial optimism regarding the war. Decades later, Ezra Pound, a fierce supporter of the fascist regime of Benito Mussolini, would dedicate a great part of his works The Cantos to the spreading of fascist, antisemitic, and pro-Axis ideas during World War II, the most notorious case within this effort being the reading of “Canto 46”, which contains explicit antisemitic and anti-American references, during a broadcast for Radio Rome. These propagandistic campaigns, first during World War I then later during World War II, would contribute to the spreading and reinforcing of nationalist tendencies on both sides, with poetics (not for the first time in the history of Literature) turning into an ally of politics.